Pembuatan alat ukur debit air menggunakan sensor aliran berbasis mikrokontroler Atmega328P - Mardani Mardani (Department of Physics – Universitas Negeri Padang UNP, 2016)
Has successfully made the water flow measuring devices using a microcontroller based flow sensor ATmega328P. This study included research into the laboratory experiments. The measurement technique does is measure directly and indirectly. Data obtained directly is the volume of water and the length of time water flows, while the data obtained indirectly is the flow of water. Based on the analysis of data can be revealed by some studies. First, the water flow measuring devices using ATmega328P microcontroller which serves to process the output of the sensor and change the sensor output with the expected output. Display the results of measurement of water flow measuring devices using LCD. The sensor used is a flow sensor that functions calculate how many liters of water out, how the water flow and how long the water flow. Second, water flow measuring devices have accuracy percentage of 94.5% sequentially, 98.5% and 97% for debit 0,11L / s. For the percentage of accuracy, at a discharge 0,11L/s and 0,05L/s is 99 % and 100 %.